2009
DOI: 10.1007/s10875-009-9301-0
|View full text |Cite
|
Sign up to set email alerts
|

Defective Solubilization of Immune Complexes and Activation of the Complement System in Patients with Pulmonary Tuberculosis

Abstract: The results obtained from the present study suggest that complement mediated solubilization is less in patients with tuberculosis, and this defective solubilization is likely to take part in a vicious cycle involving immune complex deposition and complement activation and, thus, may lead to disease progression depending on the nature of the defect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…The causes of this elevated type I IFN expression in SLE are likely deposition of ICs triggering IFNα production by plasmacytoid dendritic cells through Fc gamma receptors [19]. Elevated levels of IC accompanied by defective IC solubilization has also been documented in serum of TB patients [20] and may account, at least in part, for the similarities in gene signatures observed in both diseases. Reduced solubilization of IC also has a well-known pathological manifestation in leprosy, notably during malignant stages [21], which is caused by the mycobacterial pathogen M. leprae .…”
Section: Discussionmentioning
confidence: 98%
“…The causes of this elevated type I IFN expression in SLE are likely deposition of ICs triggering IFNα production by plasmacytoid dendritic cells through Fc gamma receptors [19]. Elevated levels of IC accompanied by defective IC solubilization has also been documented in serum of TB patients [20] and may account, at least in part, for the similarities in gene signatures observed in both diseases. Reduced solubilization of IC also has a well-known pathological manifestation in leprosy, notably during malignant stages [21], which is caused by the mycobacterial pathogen M. leprae .…”
Section: Discussionmentioning
confidence: 98%
“…Apart from a reduction in lymphocyte numbers, defects in T‐cell function and cytokine signaling have demonstrated the patients’ susceptibility to TB. The levels of C3 are usually elevated in TB infection 12 . Conversely, decreased C3 was found in lupus mimickers of Cases 2, 3 and 6.…”
Section: Discussionmentioning
confidence: 88%
“…The levels of C3 are usually elevated in TB infection. 12 Conversely, decreased C3 was found in lupus mimickers of Cases 2, 3 and 6. Although the exact mechanism is not clear, the same phenomenon was found in a Warao population with latent or active TB infection.…”
Section: Discussionmentioning
confidence: 93%
“…The late relapse in ICs levels on day 60 could be explained by the dynamics of memory B cell and plasma cell differentiation, which can secrete specific antibodies and survive without antigenic stimulation [ 38 , 39 ]. Alterations leading to constant activation of the complement system may play a role as well, and other authors have shown that, in active pulmonary TB patients, there are also abnormalities in the solubilization of ICs leading to persistent aseptic complement activation [ 40 ]. Moreover, ICs may be formed in situ in the endothelium by specific antibodies towards endothelial molecules, which react by molecular mimicry with cell wall Mtb antigens [ 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%